THU0031 Role of Polymorphonucleates in the Pathogenesis of Systemic Juvenile Idiopathic Arthritis and Still's Disease: A Proof of Concept Study. (9th June 2015) - Magnotti, F.; Lucherini, O.M.; De Clemente, C.; Talarico, R.; Emmi, G.; Galeazzi, M.; Cimaz, R.; Cantarini, L.
Abstract : Background: Systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still's disease (AOSD) are autoinflammatory disorders characterized by neutrophilia and abnormal innate immunity response [1]. It has been hypothesized a pathogenic role of neutrophils, because of patients neutrophilia, maybe related to the typical higher production of pro-inflammatory cytokines, like IL-1β, whose role in these disorders should explain the efficacy of IL-1 blockers [2, 3]. IL-1β is synthesized as inactive form and its activation is mediated by the NLRP3 inflammasome [4]. Increased release of this cytokine in the extracellular environment lead to a positive feedback loop that perpetuates and amplifies itself stimulation [5]. This mechanism as well as neutrophils' activation state could be modified in sJIA and AOSD. Objectives: Our aim was to verify possible differences between sJIA and Still's patients compared to healthy donors, in term of PMNs responsiveness to the extracellular environment and activation state. Methods: PMNs were obtained from heparinised venous blood of sJIA patients (n=6), AOSD patients (n=4) and healthy controls (HC, n=8). All patients' samples were collected during stages of active or non-active disease, according to international disease activity criteria used for the assessment of each disease. After lipopolysaccharide (LPS) treatment, IL-1β content in PMNs supernatants was measured by ELISA assay. CD11b expression levels were measured by flow cytometry, together with intracellular ROS levels through the H2 DCFDA ROS-indicator. Results: In comparison with HC, sJIA PMNs showed an increased IL-1β secretion after LPS stimulation (p<0.01). No differences were observed in AOSD patients compared to HC. About neutrophils activation state, higher intracellular ROS levels were detected in PMNs of sJIA patients (p<0.05) than HC at basal condition. Moreover, also CD11b surface marker expression levels, were higher at baseline in sJIA (p<0.01) respect HC. A similar trend was also observed in AOSD patients. Conclusions: Data from our proof of concepts study suggest a possible involvement of PMNs in the pathogenesis of sJIA and AOSD, since they seem more active respect healthy ones and more sensitive to pro-inflammatory stimuli. Although further studies are necessary to confirm and validate this hypothesis, the trend observed may have a potential role in the direction of future therapeutic studies. References: Pay, S., et al., A multicenter study of patients with adult-onset Still's disease compared with systemic juvenile idiopathic arthritis. Clin Rheumatol, 2006. 25(5): p. 639-44. Mellins, E.D., et al., Pathogenesis of systemic juvenile idiopathic arthritis: some answers, more questions. Nat Rev Rheumatol, 2011. 7(7): p. 416-26. Mavragani, C.P., et al., Adult-Onset Still's Disease: From Pathophysiology to Targeted Therapies. Int J Inflam, 2012. 2012: p. 879020. Martinon, F., et al., The inflammasomes: guardians of the body. Annu Rev Immunol, 2009. 27: p. 229-65. Frosch, M., et al., The myeloid-related proteins 8 and 14 complex, a novel ligand of toll-like receptor 4, and interleukin-1beta form a positive feedback mechanism in systemic-onset juvenile idiopathic arthritis. Arthritis Rheum, 2009. 60(3): p. 883-91. Disclosure of Interest: None declared